Indicadores de alterações auditivas em crianças com síndrome congênita do Zika vírus - Daher, Valéria Barcelos (2020)
Congenital Zika Syndrome is the result of congenital anomalies caused by Zika virus infection by vertical transmission. It is a clinical spectrum ranging from asymptomatic patients to syndromic manifestations. The aim of the study was to evaluate the risk indicators for hearing impairment in children with Congenital Zika Virus Syndrome treated at the Rehabilitation and Rehabilitation Center Dr. Henrique Santillo, from January 2015 to October 2019. The data of the clinical examination and the results of the audiological examinations were obtained by assisting patients referred to the multidisciplinary rehabilitation service by an otorhinolaryngologist. These data were presented in simple frequency. Fisher's Exact test was used at statistical analysis to assess whether the presence of another risk indicator for hearing loss was determinant in the occurrence of the hearing impairment found. For the conclusion regarding the test, the 95% confidence level was set. The most prevalent risk indicator for hearing loss in this population was neonatal jaundice. The prevalence of hearing disorders in children with ZIKV infection was 17.91% with an estimated 17.9:1000 children. These changes were not better justified by the presence of another risk indicator for hearing loss in addition to Zika virus infection. Longitudinal follow-up studies are suggested to assess the potential effects of the interaction between the virus and the host as a progressive worsening of hearing loss or the appearance of late hearing loss.